Enabling Business transformation through enterprise architecture and the knowing cycle - Smuts, Hanlie; Juleka, Busisiwe (International Journal of Engineering and Technology, 2018)
Business transformation in organizations is imperative due to the rapid and complex nature of the changes in business environments. Organizations are required to consider new strategies, innovative products and services, and adapt to disruptive and different ways of doing business to remain competitive. The nature of these changes requires holistic and strategic approaches, such as enterprise architecture, to be efficiently managed. Furthermore, the knowledge that exists in the organization, in any way that it is available, is required to develop an enterprise architecture. Knowledge management, and in particular the knowing cycle, guides the sense making capacity of an organization to understand the change that is taking place, the creation of new knowledge to address the change and informs decision making. Therefore, the purpose of this paper is to consider how enterprise architecture in association with the knowing cycle enables business transformation. Based on the findings of this study, we present a business transformation framework grounded in the alignment of the sense making processes to the establishment of an architecture vision to bracket the change situation. By applying such a framework, organizations may be guided to the best possible initiatives in order to enable business transformation and articulate the development of a future state architecture. Â